2011
DOI: 10.1016/j.eurpsy.2011.05.005
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and dimensional characteristics of euthymic bipolar patients with or without suicidal behavior

Abstract: Bipolar patients with earlier onset, mood instability (large number of depressive episodes, rapid cycling) and/or particular addictive and anxiety comorbid disorders might be at high risk of suicidal behaviour. In addition, hostility dimensions (indirect hostility and irritability), may be trait components associated with suicidal behaviour in euthymic bipolar patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 51 publications
4
39
3
1
Order By: Relevance
“…[25][26][27] Regarding suicide attempts in the bipolar group, our results were similar to international averages, which range from 11 to 19%. [28][29][30] However, we found no significant difference between bipolar patients and those with other diagnoses, in contrast with the literature. 30,31 This might be explained by the different suicide risk rates of the psychiatric disorders included in the mixed control group.…”
Section: Discussioncontrasting
confidence: 56%
“…[25][26][27] Regarding suicide attempts in the bipolar group, our results were similar to international averages, which range from 11 to 19%. [28][29][30] However, we found no significant difference between bipolar patients and those with other diagnoses, in contrast with the literature. 30,31 This might be explained by the different suicide risk rates of the psychiatric disorders included in the mixed control group.…”
Section: Discussioncontrasting
confidence: 56%
“…Table 1 provides an overview of all studies included in the final sample and of all data elements used during the data analysis process. Study designs included one case report (Kerner et al, 2013), seven transversal studies (Goldstein et al, 2012;Kheirabadi et al, 2012;Undurraga et al, 2012;De Abreu et al, 2012;Algorta et al, 2011;Evans et al, 2012;Gomes et al, 2010), nineteen cohort studies (Parmentier et al, 2012;Huber et al, 2014;Ruengorn et al, 2012;Etain et al, 2013;Cassidy, 2011;Baldessarini et al, 2012;Bellivier et al, 2011;Sears et al, 2013;Jiménez et al, 2013;Leon et al, 2012;Finseth et al, 2012;Oquendo et al, 2010;Kenneson et al, 2013;Gilbert et al, 2011;Shabani et al, 2013;Acosta et al, 2012;Song et al, 2012;Suttajit et al, 2013), and fifteen case-control studies (Eroglu et al, 2013;Antypa et al, 2013;Ryu et al, 2010;Manchia et al, 2013;Neves et al, 2010;Magno et al, 2011;Yoon et al, 2011;Arias et al, 2013;Clements et al, 2013;Kamali et al, 2012;de Moraes et al, 2013;Azorin et al, 2013;…”
Section: Resultsmentioning
confidence: 99%
“…In particular, among mental disorders, bipolar disorder is one of the leading causes of suicidal behaviors and this is a major issue in the management of the disease. About 50% of patients with bipolar disorder will experience at least one suicide attempt (Jamison, 2000) and 11-19% will commit suicide (Goodwin and Jamison, 2007;Abreu et al, 2009;Angst et al, 2005;Harris and Barraclough, 1997;Parmentier et al, 2012).…”
Section: Introductionmentioning
confidence: 98%
“…Parmentier et al (2012) [177,181] observed that reported rates of suicide attempts among women with bipolar disorders are about twice as high as among men with bipolar disorders, suggesting greater lethality of suicide attempts in men. [177,178,179,180].…”
Section: )mentioning
confidence: 99%